2008
DOI: 10.1097/mlg.0b013e3181593deb
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ototopical Antihistamine on Otitis Media in an Allergic Rat

Abstract: Ototopical antihistamines are effective in reducing effusion volume and albumin concentration in LPS-induced otitis media in an allergic rat model. This finding supports the hypothesis that ototopic antihistamines may prove effective in treating patients with allergy-induced eustachian tube dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Animal studies have noted that ototopical antihistamines are effective in reducing effusion volume and albumin concentration in lipopolysaccharide-induced otitis media in allergic rat models. This fi nding suggests that ototopical antihistamines may be effective in treating patients with allergy-induced ETD [21]. A model for how second-generation antihistamines may mitigate ETD involves their effects on histamine and muscarinic receptors.…”
Section: Antihistamine Actionmentioning
confidence: 97%
“…Animal studies have noted that ototopical antihistamines are effective in reducing effusion volume and albumin concentration in lipopolysaccharide-induced otitis media in allergic rat models. This fi nding suggests that ototopical antihistamines may be effective in treating patients with allergy-induced ETD [21]. A model for how second-generation antihistamines may mitigate ETD involves their effects on histamine and muscarinic receptors.…”
Section: Antihistamine Actionmentioning
confidence: 97%
“… 55 In addition, many studies have shown that the use of intra-aural antihistamines in sensitized rat models can reduce the accumulation of middle ear fluid, improve OME symptoms, and may be effective in treating ETD caused by allergies. 56 , 57 , 58 …”
Section: Application Of Anti-allergic Therapy In the Development Of Etdmentioning
confidence: 99%